Detecting the Efflux Pumps Gene (mexB and oprM ) in MDR Pseudomonas Aeruginosa Isolated from Wound Infection - AL-Mhesin, Wael Abbas Hameed; Abdullah, Rana Mujahid Abdullah; Okan Ürker, (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The large illnesses caused by Pseudomonas aeruginosa and the more challenging therapy for antimicrobial resistance are both due to the organism's extensive spectrum of virulence factors and several mechanisms for antibiotic resistance. The aim of the study is to detect phenotypic and genotypic efflux pump genes in Pseudomonas aeruginosa. In the current study, 100 wound samples were collected from both sexes and different ages for a period from May 2022 to November 2022 from Teaching Laboratories Hospital/Medical City, Martyr Ghazi Hariri Hospital, and Baghdad Teaching Hospital. 19 isolates of Pseudomonas aeruginosa were taken from wound infections. The samples were cultured on cetrimide agar and MacConkey agar for diagnosis, and then they underwent several microscopic, phenotypic, and biochemical tests, where included Oxidase, Indole, Urease, Glucose and Triple sugar-iron test (TSI). Pseudomonas aeruginosa susceptibility to 11 antibiotics was tested using the disc diffusion method. It has been shown that Pseudomonas aeruginosa has multi-antibiotic resistance. It showed that the bacteria isolates are resistant to Levofloxim 42%, Ciprofloxacin 40%, Piperacillin tazobactam 35%, Amicacin 32%, Ceftazidime 31%, Gentamicin 31%, Cefepime 30%, Piperacillin 29%, Tobramycin 29%, Imipenem 17%, and Meropenem 16%. The ability of bacteria to produce efflux pumps was also studied using the Ethidium Bromide Agar Cartwheel Method, where it was found that 8/19 isolates (42%) were positive. The efflux pump genes mexB and oprM were studied. The results of this study showed that all isolates of Pseudomonas aeruginosa possess mexB at 100%. While the oprM increased by 57.8%